Effective Removal of Malachite Green from Aqueous Solutions Using Magnetic Nanocomposite: Synthesis, Characterization, and Equilibrium Study - Ali Q. Alorabi (Adsorption Science & Technology)
In this work, magnetized activated Juniperus procera leaves (Fe3O4@AJPL) were successfully prepared via chemical activation of JPL and in situ coprecipitation with Fe3O4. A Fe3O4@AJPL nanocomposite was successfully applied for the elimination of malachite green (MG) dye from aqueous media. The prepared Fe3O4@AJPL adsorbent was characterized by SEM, EDX, TEM, XRD, FTIR, TGA, and BET surface area analyses. The BET surface area and pore size of the Fe3O4@AJPL nanocomposite were found to be 38.44 m2/g and 10.6 nm, respectively. The XRD and FTIR results indicated the formation of a Fe3O4@AJPL nanocomposite. Different parameters, such as pH of the solution (3–8), adsorbent dosage (10–100 mg), temperature (25–45°C), contact time (5-240 min), and initial MG concentrations (20–350 mg/L), for the elimination of the MG dye using Fe3O4@AJPL were optimized and found to be 7, 50 mg, 45°C, 120 min, and 150 mg/L, respectively. The nonlinear isotherm and kinetic studies exhibited a better fitting to second-order kinetic and Langmuir isotherm models, with a maximum monolayer adsorption capacity of 318.3 mg/g at 45°C, which was highly superior to the previously reported magnetic nanocomposite adsorbents. EDX analyses confirmed the presence of nitrogen on the Fe3O4@AJPL surface after MG adsorption. The calculated thermodynamic factors indicated endothermic and spontaneous processes. The desorption of MG dye from Fe3O4@AJPL was performed using a solution of 90% ethanol. Finally, it could be concluded that the designed Fe3O4@AJPL magnetic nanocomposite will be a cost-effective and promising adsorbent for the elimination of MG from aqueous media.